The matching effect in persuasive communication about lockdown - Giammusso, Isabella; Aquino, Antonio; Alparone, Francesca Romana; Mirisola, Alberto (Frontiers in Psychology, 2022)
Scientific literature about persuasion has shown that the effectiveness of persuasive communication may depend on the match between the affective or cognitive contents of the message and the affective (Need for Affect) or cognitive (Need for Cognition) orientation of the recipient. The present work aims to contribute to studying this effect by considering the context of health-related communication during the SARS-CoV-2 infection. Specifically, we aim to demonstrate that, when the message is characterized by affective and cognitive contents having the same (congruent message) or different valence (incongruent message), the attitude towards the target (i.e., a new lockdown) will be guided by the valence of the contents matching the individual affective/cognitive orientation. A total of 1003 participants took part in a 2 (Cognitive content message: Positive vs. Negative) x 2 (Affective content message: Positive vs. Negative) factorial design and answered an online questionnaire. Results show that people with high levels of Need for affect and low levels of Need for cognition report attitudes toward lockdown consistent with the valence of the affective contents. Conversely, attitudes of people with high levels of Need for cognition and low levels of Need for affect were not influenced by contents that matched their orientation (i.e., cognitive).